Embeddable Chloride Sensor for Monitoring Chloride Penetration into Cement Mortar - Min Zhang; Hua Fu; Li Tian; Zhenxing Du; Penggang Wang (Sensors, 2024)
A composite solid chloride sensor consisting of two single sensors, i.e., Ag/AgCl working electrode and Mn/MnO2 reference electrode, was developed. The Ag/AgCl electrode was prepared by the anodic polarization method, while the Mn/MnO2 reference electrode was prepared using the powder compaction technique. Then, the electrochemical performances such as stability, reproducibility, and sensitivity of the composite and single sensors were investigated in a saturated Ca(OH)2 solution and mortar specimen. A current density of 0.5 mA/cm2 and polarization time of 2.5 h were the optimal preparation parameters of the Ag/AgCl selective electrode. The Ag/AgCl selective electrode showed a linear potential response with the logarithm of chloride ion content in solution and had good stability, reproducibility, and anti-polarization performances. In addition, the Mn/MnO2 electrode exhibited potential stability after being activated in an alkaline solution for 60 days. The composite sensor demonstrated exceptional sensitivity to the Cl− content, boasting a slope of approximately 51.1 mV/decade, and showcased excellent stability in both solution and mortar specimens. In every measurement, the time needed for the potential of a composite sensor to become stable was less than 30 s. The sensor enables non-destructive in situ monitoring of the chloride ion content in cement mortar, thus realizing early warning of deterioration of reinforcement and guaranteeing long service life of the structure.